The role of lacteal integrity and junction transformation in obesity: A promising therapeutic target? - Xia, Qingsong; Dong, Hui; Guo, Yujin; Fang, Ke; Hu, Meilin; Xu, Lijun; Lu, Fuer; Gong, Jing (Frontiers in Endocrinology, 2022)
Lacteals are the central lymphatic vessels in the villi of the small intestine and perform nutrient absorption, especially dietary lipids, and the transportation of antigen and antigen-presenting cells. Remodeling, proliferation, and cell-cell junctions of lymphatic endothelial cells (LECs) in lacteals are the basis of the maintenance of lacteal integrity and dietary lipid absorption. Normal lipid absorption in the diet depends on sound lacteal development and proliferation, especially integrity maintenance, namely, maintaining the appropriate proportion of button-like and zipper-like junctions. Maintaining the integrity and transforming button-to-zipper junctions in lacteals are strongly connected with obesity, which could be regulated by intestinal flora and molecular signalings, such as vascular endothelial growth factor C-vascular endothelial growth receptor 3 (VEGFC-VEGFR3) signaling, Hippo signaling, Notch signaling, angiopoietin-TIE signaling, VEGF-A/VEGFR2 signaling, and PROX1. This manuscript reviews the molecular mechanism of development, integrity maintenance, and junction transformation in lacteal related to obesity.